Brain Injury Associated with Chronic Spontaneous Urticaria: a Kounis-Like Syndrome? - Luis Santiago; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
'Kounis Syndrome' is an acute coronary artery event due to an artery spasm occurring during immediate hypersensi- tivity reactions or chronic spontaneous urticaria. Recently it has been reported in other systems, including the cerebral vasculature. We present a case series of three patients observed between January 2016 and December 2018 with acute and transient brain injury associated with concomitant exacerbation of chronic spontaneous urticaria, including one patient with multiple recurrences of neurologic symptoms during exacerbations of urticaria. Minor imaging defects were observed in two patients, but there were no apparent vascular risk factors or coagulation abnormalities that might explain neurologic symptoms. Chronic spontaneous urticaria, through activation of mast cells and mediator release, seems capable of inducing cerebral arterial aggression. The authors want to call the attention to this possible association, reinforcing the need to keep urticaria under control to prevent neurological manifestations.